The Effectiveness of Using Quizizz Educational Game-Based Learning Media on the Learning Outcomes of Civil Engineering Students at the University of Muhammadiyah North Sumatra in the Subject of Kemuhammadiyahan - Nasution, Ina Zainah; Yuris, Evicenna (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This study aims to improve the learning score of Kemuhammadiyahan courses by utilizing Quizizz educational games. The research is a quantitative study using the Quasi Experimental Design method of the Nonequivalent group pretest-posttest design type. The researcher will place the research subjects into two classes which are divided into experimental and control class categories. At the beginning of the learning activities, both classes will receive a pre-test. After that, the experimental class will be treated with the Kemuhammadiyahan learning process using the Quizizz educational game-based learning method while the control class is given Kemuhammadiyahan learning with the lecture method. In the final stage, both classes will be given a post-test. In the final stage, both classes will be given a post-test. The results of the analysis show that there is an effect on improving the learning outcomes of the Quizizz educational game- based learning method on student learning outcomes in Kemuhammadiyahan learning in the experimental class. However, based on the results of research in both control and experimental classes, it can be concluded that there is no significant difference between the learning method based on Quizizz educational game- based learning method and conventional methods on student learning outcomes. This can be seen from the difference in results between the pre-test values of the control class and the experimental class by 3% and the difference in the results of the influence on the post-test value of the control and experimental classes by 2.58%.